Le Théâtre des possibles, une esthétique du potentiel (Itinera, 2019)
This study examines two examples of theatrical performances that create potential dramaturgies by constructing multiple narratives. In his “in kit” works French director Philippe Quesne establishes a “parliament” of things where the spectators can marvel at the surrounding world, while in the joyful theatre of the Flemish company De KOE multiple fictions are capable of reinventing, or even re-enchanting our present.